The Politics of Mental Health: Between Coloniality and Human Rights. A Personal Journey - Veronese, G (The Activist Practitioner, 2021)
The aim of this issue is to stand against a psychology that remains neutral in the face of racial injustice and colonisation. Any form of therapy that fails to consider justice as its core precept is insufficient. Any form of therapy that fails to recognize the ways that the political impacts on the individual is part of a system of oppression. In contemporary times, Northern European psychology can perpetuate oppression, given that it positions the individual as responsible for their own problems and fails to recognize the roles of poverty, racism and structural inequality. Much of this issue is dedicated to the perspectives of First Nations communities. If you are a Western trained therapist, this is an opportunity for you to practice humility and learn. We invite you to reflect on not only your individual practice but also how you can use your privilege to work for justice on the larger scale. In addition to First Nations' voices, other international and local friends share their journeys towards decolonization in the practice and teaching of psychology.